Developing a corpus-based maritime English dictionary for enhancing engine room crew communication - abimanto, Dhanan; Pratama, Hendi; Areni, Galuh Kirana Dwi (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
This study addresses a critical gap in maritime communication within the Indonesian context, where engine room communication typically involves a hybrid of Bahasa Indonesia and unstandardized English technical terms. While international regulations like the Standard Marine Communication Phrases (SMCP) mandate English, they do not account for this prevalent code-mixing practice, creating significant risks of miscommunication linked to maritime incidents. To mitigate these risks, this research developed a specialized, corpus-based Maritime English dictionary for Indonesian Engine Room Crew (ERC). Adopting a qualitative, corpus-aided lexicographic design, the study compiled and analyzed a corpus of authentic Indonesian engine-room texts including logbooks and technical manuals, to identify high-frequency English technical terms and their contextual usage patterns. The findings confirm the existence of a core lexicon of English terms that are systematically embedded into formulaic Bahasa Indonesia phrases, representing the functional norm of technical discourse. The resulting thematically structured dictionary, validated by subject matter experts, serves as a practical tool to standardize this critical vocabulary. The study's novelty lies in its dedicated focus on this hybrid linguistic domain, aiming to enhance communication clarity, operational safety, and the effectiveness of Maritime English training for Indonesian marine engineering personnel.